Jeffery Dahmer's Defense Mechanism in My Friend Dahmer (2017) Movie: A Psychoanalytic Approach - Khwarazmi, Dzaki Al; Amalia, Syahara Dina (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The purpose of this study is to explain how Jeffery Dahmer's defense mechanism is portrayed in My Friend Dahmer (2017) movie and analyze its effects on his character. This research uses qualitative content analysis research with a psychoanalytic approach. The result of this study indicates four types of defense mechanisms exhibited by Jeffrey Dahmer. Denial was evident as Dahmer downplayed disturbing actions, leading to increased social disconnection. Projection, showcased through dramatic performances, resulted in strained relationships and discomfort from peers. Displacement, expressed through destructive actions on preserving dead animals, generated discomfort, and disgust from those around him. Isolation, depicted in sneaking a sip of his dad's scotch and excessive alcohol consumption, emphasized Dahmer's difficulty in connecting with others. These defense mechanisms collectively contributed to negative effects, including heightened social disconnection, strained relationships, and an escalating pattern of isolation in Dahmer's life. This research is anticipated to enhance understanding of defense mechanism portrayed in My Friend Dahmer (2017) movie and aims to raise public awareness by examining Jeffery Dahmer's defense mechanism in the same film.